The Effect Of Posse (Predict, Organize, Search, Summarize, Evaluate) Strategy To The Students Ability In Reading Comprehension At Grade I In Sma Swasta Tamansiswa Tapian Dolok - Bertaria Sohnata Hutauruk; Rina Octavia Simarmata; Mandra Saragih; Febrika Dwi Lestari (EduTech: Jurnal Ilmu Pendidikan dan Ilmu Sosial, 2022)
This research is focused on the effect of POSSE (Predict, Organize, Search, Summarize, Evaluate) strategy to the students ability in reading comprehension at grade I in SMA Tamansiswa Tapian Dolok. The problem of the research are: (1) Is there any significant effect of using POSSE strategy on students ability in reading comprehension narrative text? (2) Is there any significant effect without using POSSE strategy on students ability in reading comprehension narrative text? (3) What are the effect of using POSSE strategy on students ability in reading comprehension narrative text? The researcher uses the theory (Elin (2016);Fatma (2013);Gomez (2011);Grellet (1999);Pammun (2017);Patel and Jain (2008), Ashadi (2013);Dorn and Soffos (2005);Marlini (2016);Westwood (2001), Knapp and Watkins (2005). The methodology research is quantitative research. The data of this research was collected at grade I in SMA swasta Tamansiswa Tapian Dolok. The researcher used two classes as the sample, where one class was the experimental group and the other one was the control group. The instrument for collecting data was multiple choice for both groups. The data were analyzed by applying T-Test formula. The T-test is higher than T-table (8,86 1.67) at the level sigificant is 5% (0,05) with degree of freedom (df) 60 (31+312 = 60), it means that there is an affect of using POSSE (Predict, Organize, Search, Summarize, Evaluate) strategy to the students ability in reading comprehension. The conclusion is that the students could increase their ability in comprehending narrative text by using POSSE strategy that without POSSE strategy.